Теоретические аспекты диверсификации туристических предприятий: Theoretical aspects of the travel companies diversification - Halavach, Ema; Rubakhau, Aliaksandr (Management and Administration Journal, 2021)
Strategic Enterprise Management is particularly important in a dynamic, high turbulence market of the 21st century. In conditions of modern financial crisis, enterprises run on strategies that take the need for constant change in their activities. Diversification is one of such strategy, focused on changing the product, activity or markets. The article presents the possible forms of diversification in different branches. On example of one of the companies of Brest region (Republic of Belarus), various methods and mechanisms of diversification and management in the modern world were considered.